A Human Rights Approach to Conflict Resolution. Issue 3 (2019) - Fuentes-Julio, Claudia; Ibrahim, Raslan
Abstract: Human rights and conflict resolution have been traditionally perceived as two separate fields, with contradictory principles and conflicting approaches toward achieving peace. This essay aims to understand these two fields in a more integrative way, showing how a human rights perspective can enrich the theory and practice of conflict resolution. It clarifies the main characteristics of a human rights approach to conflict resolution and identifies a set of human rights standards guiding its implementation: a normative legal framework; structural conditions for peace; participation and inclusion; and accountability and redress. The essay also briefly applies a human rights approach to the Colombian peace process and to the Oslo Accords between Israel and the Palestine Liberation Organization. The conclusion addresses one of the main criticisms of this approach and its principal challenges.